Phthalate Toxicity in Different Experimental Models - Gaur, Kajal; Siddique, Yasir Hasan (Current Biotechnology, 2025)
Phthalates (PAEs) are the major source of concern because they are commonly used plasticizers in various plastic products and can make their way into the environment. Mostly, phthalate metabolites are released in the urine. In many research studies, it has been observed that some metabolites of phthalates are more harmful than the parental compounds and can be used as biomarkers for the study of phthalate toxicity. Despite some inconsistencies, the present review describes the exposure of phthalates to children, older people, and aquatic life. The studies carried out on the toxic effects of different types of phthalates on various experimental models have been reviewed. The review also summarises the interaction between mechanisms of action involved in the toxicity induced by various PAEs. The literature search has been carried out using PubMed, Science Direct, Scopus, and Google Scholar databases. The studies available on the toxicity of phthalates from 1982 to 2024 have been considered for the review.
Keywords: oxidative stress; experimental models; DNA mutation; metabolism